Lighting installation with enhancement in illumination effectiveness / Mohd Arif Mohd Rashid - Mohd Rashid, Mohd Arif (2010)
This project presents the design of efficient lighting systems. This project will give several advantages to designers in their design to achieve an optimal illumination of lighting. The main objective of this project is to propose an efficient lighting design. This project was focusing on lighting design; due to lighting contribute the highest amount of electricity usage in a building. This project will help people to reduce the electricity usage that consumed by the lighting. The level of illumination attained must conform to the Illuminating Engineering Society (IES) Code or Jabatan Kerja Raya (JKR) Standards. The IES Code will be used in this project. The program developed is for the illumination design system for classroom, examination hall or office workspaces. The designer is required to fulfill the required information such as room's dimension, color of ceiling and color of wall. As a result, this program will automatically calculate the information needed by the designer such as room index, utilization factor, maintenance factor, number of luminaries needed, voltage drop and total saving cost. The determination of saving cost is based on comparison between the old (present) and new (suggestion) lighting designs. Thus, from this program it can help users to minimize their electricity usage according to lighting design in a building. Moreover, users are able to determine the minimum lamps used in certain room or area without reducing the quality of lighting at that place.